Base of the pyramid orientation, imitation orientation and new product performance in an emerging market. (January 2023) - Adomako, Samuel; Amankwah-Amoah, Joseph; Ahsan, Mujtaba
Abstract: This study investigates the effect of base of the pyramid (BOP) orientation on new product performance through the mediating mechanism of imitation orientation. Using time-lagged data from 505 new ventures, the results revealed that (1) BOP orientation positively influences imitation orientation, (2) imitation orientation mediates the relationship between BOP orientation and new product performance, (3) competitive intensity has a negative moderating effect on the relationship between imitation orientation and new product performance, and (4) dysfunctional competition positively moderates the effect of imitation orientation on new product performance. These findings provide a nuanced understanding of the role of BOP orientation in the context of new product performance by introducing imitation orientation as a mediating mechanism. The implications for theory development and directions for future research are discussed. Highlights: Base-of-the-pyramid (BOP) orientation and new product performance examined. BOP orientation positively influences imitation orientation. BOP orientation indirectly influences new product success through imitation orientation. Competitive intensity negatively moderates the effect of imitation orientation on the new product success. Dysfunctional competition positively moderates the effect of imitation orientation on new product success.